2000
DOI: 10.1021/jo0011383
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzo-Fused 1-Azabicyclo[m.n.0]alkanes via the Schmidt Reaction:  A Formal Synthesis of Gephyrotoxin

Abstract: The intramolecular capture of benzocyclobutyl, benzocyclopentyl, and benzocyclohexyl carbocations 7 by azides produces spirocyclic aminodiazonium ions 8, which undergo 1,2-C-to-N rearrangement with loss of dinitrogen to produce benzo-fused iminium ions resulting from either aryl (9) or alkyl (10) migration to the electron-deficient nitrogen atom. Reduction of the iminium ions affords regioisomeric benzo-fused 1-azabicyclo[m.n.0]alkanes, e.g., benzopyrrolizidines, benzoindolizidines, benzoquinolizidines, or per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(44 citation statements)
references
References 68 publications
2
41
0
1
Order By: Relevance
“…An intramolecular Schmidt reaction with formation of 2,3‐dihydropyrrolo[1,2‐ a ]indole 282 was studied . It was demonstrated that the interaction between azide 283 and trifluoromethylsulfonic acid proceeds via formation of intermediate aminodiazonium ion 284 and 1,2 CN rearrangement followed by the elimination of N 2 leading to the indolinium salts.…”
Section: Introductionmentioning
confidence: 99%
“…An intramolecular Schmidt reaction with formation of 2,3‐dihydropyrrolo[1,2‐ a ]indole 282 was studied . It was demonstrated that the interaction between azide 283 and trifluoromethylsulfonic acid proceeds via formation of intermediate aminodiazonium ion 284 and 1,2 CN rearrangement followed by the elimination of N 2 leading to the indolinium salts.…”
Section: Introductionmentioning
confidence: 99%
“…An X-ray crystallographic analysis of enantiopure 3 m disclosed the absolute configuration as R. [14] Notably, as evidence for the proposed reaction pathway (Scheme 1), the intermediate 4 could be isolated. An X-ray crystallographic analysis of enantiopure 3 m disclosed the absolute configuration as R. [14] Notably, as evidence for the proposed reaction pathway (Scheme 1), the intermediate 4 could be isolated.…”
mentioning
confidence: 89%
“…In this way, gephyrotoxin, a naturally occurring substance isolated from the secretions of the poison-dart frog Dendrobates histrionicus, was prepared [157]. 17.1.5 General Reactivity: Useful Reactions 17.1.5.1 Addition to Nitrogen As in pyridine, the nitrogen in quinoline undergoes protonation, alkylation, acylation, N-amination [158], and with peroxyacids or in the presence of other oxidative systems, such as O 2 /2-methylpropanal [159], oxidation to the N-oxide.…”
Section: Cycloaddition Processesmentioning
confidence: 99%